A liquid chromatography-tandem mass spectrometry based method for the quantification of adenosine nucleotides and NAD precursors and products in various biological samples - Hiefner, Johanna; Rische, Johann; Bunders, Madeleine J.; Worthmann, Anna (Frontiers in Immunology, 2023)
Adenine nucleotides (AN) are ubiquitous metabolites regulating cellular energy metabolism and modulating cell communication and inflammation. To understand how disturbances in AN balance arise and affect cellular function, robust quantification techniques for these metabolites are crucial. However, due to their hydrophilicity, simultaneous quantification of AN across various biological samples has been challenging. Here we present a hydrophilic interaction high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) based method for the quantification of 26 adenosine nucleotides and precursors as well as metabolic products of NAD in plasma, liver, and adipose tissue samples as well as cell culture supernatants and cells. Method validation was performed with regards to linearity, accuracy, precision, matrix effects, and carry over. Finally, analysis of cell culture supernatants derived from intestinal organoids and RAW 264.7 cells illustrates that the here described method is a reliable and easy to use tool to quantify AN and opens up new avenues to understand the role of AN generation and breakdown for cellular functions.